The impact of autobiographical memory on brand retrieval and purchase intention. Issue 5 (14th January 2021) - Stocchi, Lara; Wright, Malcolm; Fuller, Rachel
Abstract: Autobiographical memory involves mentally reliving past episodes that are personally relevant. Psychology research shows that it has remarkable bearing on one's life, including the accomplishment of tasks, self‐enhancement, self‐preservation and attaining goals. Yet, the understanding of autobiographical memory in consumer behaviour research is much more limited. Accordingly, the present study evaluates the impact of two cognitive mechanisms resulting from personal past‐usage experiences linked to the product category, which are likely to underpin consumers' retrieval of brands from memory and purchase intention. The two cognitive aspects are: the cued recollection of specific autobiographical memories; and the accessibility (in memory) of autobiographical episodes of consumption that form product category knowledge. The empirical results obtained across three online experiments suggest product category knowledge accessible in consumer memory has a greater effect on brand retrieval and purchase intention than the direct recollection of specific autobiographical memories cued by the product category. Perceived importance of choice moderates this effect, which primarily concerns purchase intention. In particular, consistent with prior research on activation confusion, product category knowledge reduces purchase intention, especially for highly familiar (or prototypical) brands. Accordingly, we outline implications for branded communications, and advertising pre‐ and post‐testing.